2005
DOI: 10.1007/s00256-005-0948-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiological assessment of lumbosacral dystrophic changes in high-grade spondylolisthesis

Abstract: Analysing specific criteria, we think it is possible to note progressive dystrophic changes according to the natural history of lumbosacral spondylolisthesis. We think that repeated measurements of these morphological parameters in patients diagnosed with a low-grade lumbosacral spondylolisthesis could be helpful in the early detection of evolving lumbosacral kyphosis and L5 slipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[9][10][11][12][13][14] Five studies reported a correlation between PI and slip grade, [9][10][11][12][13] all finding that PI was significantly higher in spondylolisthesis patients compared to controls (e.g. 76° vs. 48.2-53.2°, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] Five studies reported a correlation between PI and slip grade, [9][10][11][12][13] all finding that PI was significantly higher in spondylolisthesis patients compared to controls (e.g. 76° vs. 48.2-53.2°, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…S1 remodeling by dysplastic L5 and loss of L4 and S1 articulation makes border identification dificult. Vialle et al noted that patients with low SS had a more easily reduceable spondylolisthesis 14 and that SS, PT, and LL measurements in HGS were compensatory for high PI. 13 Schuller et al found that BMI was significantly higher in a spondylolisthesis group compared to control and suggested that increased PT in HGS patients most likely results from a compensatory posterior pelvic tilt.…”
Section: -14mentioning
confidence: 99%
“…We, therefore, recommend the use of the posterior border of S1 as the landmark to measure Dubousset's LSA. With progression of slippage, the inferior endplate of L5 tends to become dysplastic [19,28] and the L5 vertebral body may adopt a trapezoidal shape [31]. Moreover, remodeling of the S1 endplate can occur and is referred to as sacral doming or rounding [20,31] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] On the opposite, measurement techniques 5,6,14 that only express the relative position or shape of the dome have no clear association with slip grade. Second, results have shown that the SDSG index is in agreement with the clinical knowledge and perspectives of the 5 spine surgeons involved in this study.…”
Section: Discussionmentioning
confidence: 99%